Demand patterns for treatment insurance in Norway - Karl Ove Aarbu (Center for Economic Studies and ifo Institute (CESifo), 2010)
In Scandinavia, the provision of health care services has been, almost entirely, the responsibility of the public health care system. However, in the last five to seven years there has been remarkable growth in the private health care market. These health care services are obtained normally through insurance contracts. In this paper, I seek explanations for this phenomenon, using data from Norway. First, using available market data, I document that the market for private treatment insurance-often labelled as 'jump the treatment queue insurance'-is growing rapidly. Thereafter, I present a theoretical model that identifies primary drivers for individual demand for treatment insurance. The third step is to analyse a unique survey data set that is combined with aggregate county data on treatment queues. The overall results indicate that public waiting lists affect the demand for privately bought insurance, while employer-provided insurance does not seem to be affected. I find strong preference for this type of insurance among smokers and the self-employed. Moreover, income is an important determinant of insurance demand.
Keywords: I11; I12; I18; H51; 330; Private Krankenversicherung; Nachfrage; Gesundheitsversorgung; Norwegen